Camouflaging endovascular stents with an endothelial coat using CD31 domain 1 and 2 mimetic peptides - Jean Sénémaud, MD, PhD; Charles Skarbek, PhD; Belen Hernandez, PhD; Ran Song, PhD; Isabelle Lefevre, PhD; Elisabetta Bianchi, PhD; Yves Castier, MD, PhD; Antonino Nicoletti, PhD; Christophe Bureau, PhD; Giuseppina Caligiuri, MD, PhD (JVS - Vascular Science)
Objective: Implantation of an endovascular device disrupts the homeostatic CD31:CD31 interactions among quiescent endothelial cells (ECs), platelets, and circulating leukocytes. The aim of this study was to design an endothelial-mimetic coating of nitinol and cobalt-chromium (CoCr) surfaces and stents using synthetic CD31 peptides, to promote device endothelialization and pacific integration within the arterial wall. Methods: Peptides mimicking the domains 1 (D1) and 2 (D2) of CD31 were synthetized and immobilized onto experimental nitinol and CoCr surfaces using a three-step, dip-coating, mussel-inspired protocol using copper-free click chemistry. Human aortic EC phenotype and endothelialization assessment using parallel scratch tests were carried out using five synthetic CD31 peptides coated on 4.8-mm nitinol and CoCr flat disks and were compared with control disks. The CD31 peptide exhibiting the best results in vitro was then immobilized on clinical-grade 3 × 40-mm self-expanding nitinol and 2.5 × 20.0-mm balloon-expandable CoCr stents. Such devices were implanted in native arteries of White New Zealand rabbits, and compared with control uncoated bare metal stents (BMS) and drug-eluting stents 7 and 30 days after implantation using resin cross-sections and scanning electron microscopy (n = 2-3 per group at each time point). Results: Membrane-distal CD31 D1 and D2 peptides exhibited a distinct capability to foster a healthy endothelial phenotype and to promote endothelialization in vitro. By day 7 after implantation, CD31 nitinol and CoCr stents were evenly covered by wholesome ECs, devoid of thromboinflammatory signs, in contrast with both BMS and drug-eluting stents. Such results were consistent until day 30. Conclusions: Membrane-distal CD31 biomimetic peptides seem to camouflage the device surface effectively, preventing local reactions and promoting rapid and seamless endovascular integration. : Clinical Relevance: Despite significant technical advancements, the challenge of vascular stent healing persists. In this preclinical study, we developed a novel endothelial-mimetic coating inspired by the trans-homophilic portion of CD31, a glycoprotein predominantly expressed by endothelial cells and pivotal in circulatory homeostasis. After successive peptide design and surface functionalization, both in vitro and in vivo experiments demonstrated the potential of the CD31-coated surface to promote the acquisition of a physiological endothelial cell phenotype, facilitating rapid healing and peaceful integration of stents. Further studies with larger sample sizes, extended follow-up periods, and assessment of the impact on in-stent restenosis are essential before translating this strategy to clinical applications.